KAJIAN PENGGUNAAN JEMBATAN PENYEBERANGAN ORANG TERHADAP KESELAMATAN PEJALAN KAKI DI KOTA BALIKPAPAN - Mulya, Widya; Zainul, L.M; Alifah, Rifda Nur (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Transportation safety is a condition where the requirements are met so that everyone avoids the risk of accidents during travel caused by humans, transportation modes of transportation and the environment. Pedestrian safety is part of transportation safety, so it needs to be supported by good infrastructure, one of which is the People's Crossing Bridge (JPO). There is only 1 pedestrian bridge in the city of Balikpapan and it was built around 2005 which is located in the center of the shopping center area of ​​Plaza Balikpapan on Jalan Jenderal Sudirman, while the population in the city of Balikpapan continues to increase every year. The purpose of this study was to determine the use of pedestrian bridges for pedestrian safety. The research method used is using a qualitative descriptive method, to find out and describe descriptively the use of pedestrian bridges for pedestrian safety in the city of Balikpapan where the authors use observation sheets regarding the physical condition of the JPO and by using interview guidelines. All data that has been collected in this study will be processed and analyzed in a descriptive form regarding the use of pedestrian bridges including security and pedestrian safety for pedestrian crossing users in the city of Balikpapan. The results showed that the pedestrian safety condition on the pedestrian bridge in Balikpapan obtained a percentage of 67% and the pedestrian safety condition on the pedestrian bridge in Balikpapan obtained a percentage of 75% and could be categorized as GOOD. Keywords: pedestrian bridge, security, pedestrian safety